Automation of lettuce seedlings irrigation with sensors deployed in the substrate or at the atmosphere - Ana Carolina Mendes Bezerra; David da Cunha Valença; Daniel Fonseca de Carvalho; Camila Ferreira de Pinho; Fernanda Reinert; Daniela Pinto Gomes; Fernanda Palmeira Gabetto; Ricardo Antunes Azevedo; Daniele Masseroni; Leonardo Oliveira Medici (Scientia Agricola)
ABSTRACT: Seedling production is an important step in the lettuce production system. However, there is a tendency to apply excessive irrigation at this stage. The aim of this study was to test the use of the Simplified Irrigation Controller (SIC) under two conditions: first, with the sensor installed in the substrate (measuring the soil water tension) and second, in the atmosphere (“atmospheric” - responding to vapor demand in the atmosphere) to control the irrigation of lettuce seedlings. The performance of the SIC was evaluated by monitoring plant traits. The lettuce seeds of the Regina cultivar were sown in styrofoam trays with commercial organic substrate. Both experiments were conducted under greenhouse conditions and evaluated under different SIC activation tensions. Shoot fresh weight and dry weight, height, number of leaves, leaf length, leaf area, water use efficiency (WUE) (ratio between the dry mass of plant produced by the volume of water applied), chlorophyll content, stomatal conductance and chlorophyll a fluorescence were assessed. In the experiment with the substrate sensor, the tension of 11.5 kPa caused death in 94 % of the seedlings and was disregarded in the statistical analysis. All biometric and physiological traits evaluated decreased as the SIC tensions increased. Thus, tensions of 4.0 (substrate sensor) and 3.5 kPa (atmospheric sensor) showed greater potential for producing vigorous seedlings, with WUE average values of 1.86 and 1.37 g L−1, respectively. Cultivation of lettuce seedlings proved viable under both conditions when the SIC was used, with the emergence of a number of practical advantages of the atmospheric sensor over the substrate one.